2016
DOI: 10.1007/978-3-319-45174-9_9
|View full text |Cite
|
Sign up to set email alerts
|

Classification-Based Causality Detection in Time Series

Abstract: Brain effective connectivity aims to detect causal interactions between distinct brain units and it can be studied through the analysis of magneto/electroencephalography (M/EEG) signals. Methods to evaluate effective connectivity belong to the large body of literature related to detecting causal interactions between multivariate autoregressive (MAR) data, a field of signal processing. Here, we reformulate the problem of causality detection as a supervised learning task and we propose a classification-based app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…The remaining part of the dataset was used to estimate the quality of predictions, both for the proposed method and for the Granger Causality Analysis (GCA, see Barnett and Seth, 2014 ) method (see section 3), for comparison. In the second part of this section, we briefly present the proposed classification-based method for predicting causality, following Benozzo et al ( 2016 , 2017 ). Before the second part, we define the multivariate autoregressive (MAR) model, that we use for generating a second dataset to further characterize the proposed method, and a traditional causality measure: the Geweke index, on which GCA is based.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The remaining part of the dataset was used to estimate the quality of predictions, both for the proposed method and for the Granger Causality Analysis (GCA, see Barnett and Seth, 2014 ) method (see section 3), for comparison. In the second part of this section, we briefly present the proposed classification-based method for predicting causality, following Benozzo et al ( 2016 , 2017 ). Before the second part, we define the multivariate autoregressive (MAR) model, that we use for generating a second dataset to further characterize the proposed method, and a traditional causality measure: the Geweke index, on which GCA is based.…”
Section: Methodsmentioning
confidence: 99%
“…The method presented in this work builds on our previous work (see Benozzo et al, 2016 , 2017 ), where we developed a conceptually similar paradigm applied to a simple MAR model, rather than to a complex biophysical model of neural interactions. There, we proposed a novel feature space to encode the multivariate timeseries and showed that effective connectivity could be predicted at even better rates than those of state-of-the-art solutions.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, we report the details of the solution computed with the supervised method that we submitted to the Biomag2014 Causality Challenge (Causal2014)b 1 , which reached the second place of the ranking (Benozzo et al, 2016 ). Such competition adopted an autoregressive model as generative process to simulate brain signals.…”
Section: Introductionmentioning
confidence: 99%